2001
DOI: 10.1113/eph8602146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Direct Sympathetic and Vagus Nerve Stimulation on the Physiology of the Whole Heart – A Novel Model of Isolated Langendorff Perfused Rabbit Heart with Intact Dual Autonomic Innervation

Abstract: It is well recognised that stimulation of the sympathetic nervous system exerts a positive chronotropic effect on the heart, speeding the rate of discharge of the intrinsic pacemaker, which is usually the sino-atrial node, whilst parasympathetic stimulation has opposite effects (Levy & Zieske, 1969). Atrioventricular (AV) conduction is also affected, with sympathetic stimulation speeding conduction (positive dromotropy) and parasympathetic stimulation delaying conduction (negative dromotropy) (Warner et al. 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
143
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(162 citation statements)
references
References 19 publications
13
143
0
2
Order By: Relevance
“…(Brack et al, 2006) Baseline heart rates were markedly greater in our study than in previous studies (perhaps due to improved perfusion) and so it stands to reason that hearts may be initially operating on the downward slope of the bi-phasic force-frequency curve. (Brack et al, 2006;Ng et al, 2001;Winter et al, 2015) However, we cannot rule out that the positive inotropic response to VNS reflects the low oxygen carrying capacity of the Krebs buffer and resulting improved energetics when heart rate is slowed. The influence of hyoscine and physostigmine on the inotropic response to VNS are likely to be secondary to effects on heart rate (i.e.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…(Brack et al, 2006) Baseline heart rates were markedly greater in our study than in previous studies (perhaps due to improved perfusion) and so it stands to reason that hearts may be initially operating on the downward slope of the bi-phasic force-frequency curve. (Brack et al, 2006;Ng et al, 2001;Winter et al, 2015) However, we cannot rule out that the positive inotropic response to VNS reflects the low oxygen carrying capacity of the Krebs buffer and resulting improved energetics when heart rate is slowed. The influence of hyoscine and physostigmine on the inotropic response to VNS are likely to be secondary to effects on heart rate (i.e.…”
Section: Discussionmentioning
confidence: 94%
“…(Möller et al, 1999) The finding that VNS caused an increase in LVP appears at odds with previous reports suggesting that vagal stimulation decreases ventricular force in the rabbit heart. (Brack et al, 2006;Ng et al, 2001;Winter et al, 2015) However, Ng et al (2006) reported a bi-phasic force-frequency response, consisting of an initial increase followed by a secondary decrease in ventricular force with increasing heart rate. (Brack et al, 2006) Baseline heart rates were markedly greater in our study than in previous studies (perhaps due to improved perfusion) and so it stands to reason that hearts may be initially operating on the downward slope of the bi-phasic force-frequency curve.…”
Section: Discussionmentioning
confidence: 99%
“…In order to investigate the mechanisms underlying the autonomic modulation of VF, our group developed an in vitro Langendorff perfused innervated rabbit heart preparation (Ng et al 2001b) which allows controlled stimulation of autonomic nerves without the confounding influence of underlying tonic autonomic activity, haemodynamic reflexes, circulating hormones or anaesthetics. Stimulating sympathetic inputs from within the spinal cord, reduced the stimulus current required to induce VF i.e.…”
Section: Sympathetic Nerve Stimulation Apd Restitution and Vfmentioning
confidence: 99%
“…Using the innervated heart preparation (Ng et al 2001b), our group studied the effects of VNS on electrical restitution and VFT (Ng 2014). …”
Section: Direct Anti-vf Protection -Studies In the Isolated Innervatementioning
confidence: 99%
“…In addition, the proportion of conflict trials across a task block was manipulated, using low-conflict (75% no-conflict and 25% conflict trials) and high-conflict (25% no-conflict and 75% conflict trials) task blocks that were presented in alternating order. On the basis of the known temporal dynamics of beta-adrenergic influence on the heart (Mokrane & Nadeau, 1998;Ng, Brack, & Coote, 2001), it is expected that the effects of trial conflict on RZ only emerge after 1 to 3 seconds following stimulus onset. On the other hand, based on earlier studies it is expected that the effect of trial conflict on cardiac deceleration emerges approximately 1 second after stimulus onset (i.e., the first interbeat interval following stimulus onset) and lasts for about 1 second (Fiehler et al, 2004;Jennings et al, 1991;Spapé & Ravaja, 2016).…”
Section: Introductionmentioning
confidence: 99%